A Simplified Classification of the Relative Tsunami Potential in Swiss Perialpine Lakes Caused by Subaqueous and Subaerial Mass-Movements - Strupler, Michael; Evers, Frederic M.; Kremer, Katrina; Cauzzi, Carlo; Bacigaluppi, Paola; Vetsch, David F.; Boes, Robert M.; Fäh, Donat; Anselmetti, Flavio S.; Wiemer, Stefan (Frontiers in Earth Science, 2020)
Historical reports and recent studies have shown that tsunamis can also occur in lakes where they may cause large damages and casualties. Among the historical reports are many tsunamis in Swiss lakes that have been triggered both by subaerial and subaqueous mass movements (SAEMM and SAQMM). In this study, we present a simplified classification of lakes with respect to their relative tsunami potential. The classification uses basic topographic, bathymetric, and seismologic input parameters to assess the relative tsunami potential on the 28 Swiss alpine and perialpine lakes with a surface area > 1 km2. The investigated lakes are located in the three main regions “Alps”, “Swiss Plateau”, and “Jura Mountains”. The input parameters are normalized by their range and a k-means algorithm is used to classify the lakes according to their main expected tsunami source. Results indicate that lakes located within the Alps show generally a higher potential for SAEMM and SAQMM, due to the often steep surrounding rock-walls, and the fjord-type topography of the lake basins with a high amount of lateral slopes with inclinations favouring instabilities. In contrast, the missing steep walls surrounding lakeshores of the “Swiss Plateau” and “Jura Mountains” lakes result in a lower potential for SAEMM but favour inundation caused by potential tsunamis in these lakes. The results of this study may serve as a starting point for more detailed investigations, considering field data.